Cost-benefit of anthelmintic protocols in naturally infected sheep - Balzan A.* (2014)
Background: Gastrointestinal nematode infections are a major problem for sheep production, leading to large economic losses as a result of the high costs for prevention and treatment. In helminthiasis, the most common clinical signs are weight loss, submandibular edema, diarrhea, and anemia. Among the many nematodes, stands out in the Brazilian states Haemonchus contortus and Trichostrongylus colubriformis, as well as these parasites have developed a number of anthelmintic resistance. Therefore, the aim of this study was to evaluate the cost-benefit of different antihelminthic protocols in naturally infected sheep. Material, Methods & Results: The study was conducted for one year in a sheep farm located in Southern Brazil. Three groups (A, B and C) with 10 adult sheep each were used. The group A was treated without drug rotation, and levamisole hydrochloride was used at intervals of 60 days. The group B was treated with levamisole hydrochloride at months 2, 4, 8 and 12 and albendazole at month 6 (antiparasitic treatment with pharmacological rotation). Animals from the group C were treated after selection by the Famacha method, which is based on the degree of anemia of their mucous ocular membranes. The results showed that the animals of the group C had lower values of eggs per gram of feces (EPG), and thus, they were treated more efficiently. The main genera of the Trichostrongylidae family observed in this study were Haemonchus, Trichostrongylus, and Teladorsagia, but were no difference between groups related to the percentage of helminths the Trichostrongylidae family. Furthermore, it was found that the cost of anthelmintic protocols used for groups B and C was 7.4 and 49.6% less than the cost of the methods used in the group A, respectively. We have noted that if all the animals were treated based on the Famacha method with levels 4 and 5, only 20 (group A) and 22 (group B) animals would have received treatment, which characterizes an unnecessary cost of 66.6 and 63.3% for group A and B, respectively. The group C showed the lowest number of eggs per gram of feces, indicating greater treatment efficiency when compared to group A. Discussion: Some methods are used to control nematodes including Famacha, which is related to hematophagous helminths and its most significant advantage is the reduction of the number of treatments needed, reducing the chances of helmintic resistance, as observed in the current study. In this research it was found that the EPG counts were reduced after treatment, but it was not zero in most animals, which indicates a degree of resistance. The resistance can be defined as the decrease in the efficacy of a drug against the parasite population that is generally susceptible, an evident fact in this study for H. contortus and Trichostrongylus sp. According to researchers, resistant parasites are probably in a lower number, but the selection pressure exerted by a given drug may favor the increase of resistant on individuals in the same population of parasites that were originally susceptible to the treatment. Therefore, the existence of an anthelmintic treatment program is important in a herd, in order to delay the occurrence of resistance and for better production performance. The Famacha method minimizes the use of antihelmithics and in addition, it mitigates the possibility of drug residues on meat, milk and the environment. Therefore, it is possible to conclude that the Famacha method showed the best cost-benefit response, with lower treatment costs to producers, and consequently, it minimized the chances of drug residues in animal products and in the environment.